(3TQM gOGjI GdMceIs - (3ejQ MSjf Hf eYjf GdOjf GdejHPi Ydj eGShis; (3GKjQ GdOjf GdGHgQj , GdeaVd Hf YeQ Hf GdeaVd GdGHgQj GdSeQbfOj,J (B663 (3g` s ((3eUWai GdSYjO s)
(3ChdgG (B:s
(3hHYO jbhd GdeYJUe HdWag GdCHOi MSjf Hf eYjf GdOjf GdejHOi s
(3BNQgG (B:s
(3Ef GdhGLH Ydi GdMb eWGdYI cJH GdTjNjf CHj Ydi hTgGH GdOjf GdeYJRd s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B279 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B315s
Keywords: (3GdadSaI hGdefWbs